2020
DOI: 10.1093/ibd/izaa315
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Adherent Invasive E. coli LF82 With Human α-defensin 5 in the Follicle-associated Epithelium of Patients With Ileal Crohn’s Disease

Abstract: Background The first visible signs of Crohn’s disease (CD) are microscopic erosions over the follicle-associated epithelium (FAE). The aim of the study was to investigate the effects of human α-defensin 5 (HD5) on adherent-invasive Escherichia coli LF82 translocation and HD5 secretion after LF82 exposure in an in vitro model of human FAE and in human FAE ex vivo. Methods An in vitro FAE-model was set up by the coculture of Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Vitamin D3-deficient mice treated with DSS showed significant epithelial dysfunction and increased colitis susceptibility, aggravating the damage caused by AIEC colonization. Thus, vitamin D deficiency after AIEC infection may disrupt the mucosal barrier, leading to increased susceptibility to mucosal damage and an increased risk of IBD[ 111 ].…”
Section: Aiec In Ucmentioning
confidence: 99%
“…Vitamin D3-deficient mice treated with DSS showed significant epithelial dysfunction and increased colitis susceptibility, aggravating the damage caused by AIEC colonization. Thus, vitamin D deficiency after AIEC infection may disrupt the mucosal barrier, leading to increased susceptibility to mucosal damage and an increased risk of IBD[ 111 ].…”
Section: Aiec In Ucmentioning
confidence: 99%
“…33 In the human gut, α-defensin proteins, including α-defensin 5 and α-defensin 6, are the most abundant, diverse, and highly expressed antimicrobial proteins. 34 Previous studies have shown that α-defensin has spectral bactericidal activity against gram-positive and gram-negative bacteria and, in some instances, against fungi, viruses, and protozoa. 35 However, few studies have focused on the exact impact of fecal stream deprivation on the secretion of antimicrobial peptides in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has recently emerged indicating that antimicrobial peptides secreted by Paneth cells have vital roles in innate enteric immunity and in the regulation of intestinal microbiota 33 . In the human gut, α‐defensin proteins, including α‐defensin 5 and α‐defensin 6, are the most abundant, diverse, and highly expressed antimicrobial proteins 34 . Previous studies have shown that α‐defensin has spectral bactericidal activity against gram‐positive and gram‐negative bacteria and, in some instances, against fungi, viruses, and protozoa 35 .…”
Section: Discussionmentioning
confidence: 99%